Pengembangan Aplikasi Relaksasi Guided Imagery Berbasis Android Untuk Tingkat Stres Pada Pasien Pra Lansia dengan Hipertensi - Sari, Purwanti Nurfita; Haryanto, Joni; Sari, Dianis Wulan (Universitas Tribhuwana Tunggadewi, 2023)
Chronic stress in hypertensive patients results in fatal complications. Information technology is more effective than face-to-face communication for stress management. It has been demonstrated that media technology is more appealing, of high quality, effective, and efficient. The goal of this study is to create a guided imagery app for Android that will help pre-elderly hypertensive patients feel less stressed. A research and development design was used for this project. In addition to application development through focus group discussions and professional consultations, as well as assessing the viability of utilizing the application, exploration of stress levels and evaluation of stress management are monitored. The study's older participants, who ranged in age from 45 to 59, had hypertension. 50 patients were involved in phase 1 data collecting utilizing the perceived stress scale questionnaire. 30 patients in phase 2 used a system usability scale questionnaire, which was modified and tested for validity again with 10 respondents. The inclusion criteria for primary hypertension patients undergoing treatment were pre-elderly, aged 45–59 years old, male and female, Muslim, able to read and write, own a smartphone and be able to operate it, and have no visual or hearing limitations. Purposive sampling was used and data was analyzed using descriptive data analysis. The results show a moderate level of stress (62%). The results of the due diligence got a value of 80.66 (good and proper). The development of an Android-based guided imagery relaxation application can be recommended to pre-elderly hypertensive patients as a medium that can be used independently at home to help control stress levels.